If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 143 + -9x Reorder the terms: 7 + 6x = 143 + -9x Solving 7 + 6x = 143 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 7 + 6x + 9x = 143 + -9x + 9x Combine like terms: 6x + 9x = 15x 7 + 15x = 143 + -9x + 9x Combine like terms: -9x + 9x = 0 7 + 15x = 143 + 0 7 + 15x = 143 Add '-7' to each side of the equation. 7 + -7 + 15x = 143 + -7 Combine like terms: 7 + -7 = 0 0 + 15x = 143 + -7 15x = 143 + -7 Combine like terms: 143 + -7 = 136 15x = 136 Divide each side by '15'. x = 9.066666667 Simplifying x = 9.066666667
| 9x-16=6x-2 | | x-21=7 | | 4x^2=-5 | | -258=m-587 | | x^2-2x+7=7 | | 25+4m=2m+65 | | 68-7x=20x+20 | | x+26=45 | | 8-9x=88-37x | | s-904=-615 | | 8-9x=88-27x | | x-26=45 | | 2x+27=5x-9 | | s-2=31 | | 8(3n-2)=(6n+2)+4 | | -18-4x=6-8x | | 174-4x=23x+18 | | 8a+5a+5b-3b= | | 2x+20=9x-27 | | -16=0.2n | | 3/5=6 | | 122-3x=15x+24 | | 5(3x+1)=4x-8x | | 1+4m+5m^2+2m^3=0 | | 1-3+7=6 | | 5u-10v= | | 12-9x=35-16x | | x^3-9x^2+24x+1=0 | | 4+3*5=x | | 4x-x-2=34 | | 3bc=12+9bc | | s+808=57 |